Alkaline-promoted Co-Ni bimetal ordered mesoporous catalysts with enhanced coke-resistant performance toward CO2 reforming of CH4. (March 2017) - Xu, Leilei; Wang, Fagen; Chen, Mindong; Fan, Xiaolong; Yang, Haoming; Nie, Dongyang; Qi, Lu
Graphical abstract: Highlights: Alkaline-promoted Co-Ni bimetal mesoporous materials prepared by one-pot EISA method. Thermal sintering of Co-Ni metals inhibited by confinement effect of mesostructure. Alkaline promotors improved the catalytic activity and stability by surface basicity. Enhanced coke-resistance due to intensified chemisorption and activation of CO2 . Abstract: The Co-Ni bimetal based catalysts had been considered as promising candidates for the CO2 reforming of CH4 reaction due to the Co-Ni synergistic effect. In order to further improve the catalytic property and anti-coke performance, Mg and Ca alkaline-promoted Co-Ni bimetal ordered mesoporous materials had been designed and fabricated by one-pot evaporation induced self-assembly method, which could be directly used as the catalysts for CRM reaction. These mesoporous catalysts were systematically characterized by XRD, N2 adsorption-desorption analysis, TEM, EDS, XPS, H2 -TPR, and CO2 -TPD. It was found that the materials calcined at 700 °C could successfully maintain relatively large surface areas (120–212 m 2 /g), big pore volumes (0.27–0.48 cm 3 /g), and narrow pore size distribution (9.5–11.0 nm), which could accommodate the gaseous feedstock with sufficient accessible Co-Ni active centers. Meanwhile, the Co-Ni active centers were in situ introduced into and confined by the ordered mesoporous framework by one-pot strategy, which could effectively inhibit the thermal agglomeration of Co-Ni nanoparticles. The presence of the Mg and Ca basic modifiers greatly intensified the surface basicity and enhanced the chemisorption of CO2, which would be beneficial to the activation of CO2 and the acceleration of the coke-elimination process. The present Co-Ni bimetal catalysts promoted by Mg and Ca displayed higher catalytic activities and better coke-resistant performance than the Co-Ni reference catalyst without any alkaline modification. Therefore, the present Mg and Ca alkaline elements promoted Co-Ni bimetal based ordered mesoporous catalysts promised potential candidates for CRM reaction.